Analysis Of Sharia Financial Aspects In Baitul Maal Wa Tamwil During Covid-19 Pandemic - Nasrulloh, Agus Ahmad; Wijaya, Trisna (Univeristas Islam Bandung, 2023)
This study aims to examine the impact of the Covid-19 pandemic on the financial aspects of BMTs or Baitul Maal wat Tamwil (sharia cooperatives) in Tasikmalaya, as well as finding solutions deemed appropriate according to respondents’ agreement. The method used is the Analytic Network Process (ANP). The results of the study show that there are three elements in the financial aspects affected by the pandemic. The first is liquidity. The pandemic caused a high number of problematic financing, hence the solution is limiting financing approval. The second is profitability. To boost the already-low availability of funds, a BMTs should sell unproductive assets. Lastly is the third party funding. The drop in creditors’ level of confidence must be solve by fostering public trust. The implication of this study will improve the financial condition of BMT, so it can rise from the downturn due to the pandemic.